2019
DOI: 10.7717/peerj.7692
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of picture format on children’s naming responses

Abstract: Digital photography has facilitated the use of more ecological stimuli than line drawings as experimental stimuli. However, there is lack of evidence regarding the effect of the picture format on children’s naming agreement. The present work investigated whether the format of presentation of the pictures (line drawing or photograph) affects naming task performance in children. Two naming task experiments are reported using 106 concepts depicted both as a photograph and as a matched drawing delineated directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Some methodological changes were introduced. First, it has been demonstrated that photographs increase name agreement and correct response rates in comparison to black-and-white drawings in both adults (Salmon et al, 2014) and children (Martínez & Matute, 2019). Thus, to reduce stimulus-specific effects, color photographs were used in Study 2.…”
Section: Resultsmentioning
confidence: 99%
“…Some methodological changes were introduced. First, it has been demonstrated that photographs increase name agreement and correct response rates in comparison to black-and-white drawings in both adults (Salmon et al, 2014) and children (Martínez & Matute, 2019). Thus, to reduce stimulus-specific effects, color photographs were used in Study 2.…”
Section: Resultsmentioning
confidence: 99%
“…We provide norms for two different picture formats (photographs and line drawings). Note, however, that we did not use an experimental design in order to examine differences between formats, because previous literature has already shown that line drawings and photographs have different characteristics that can affect naming performance in children [ 9 ] and in adults [ 7 ]. To consult detailed norms for each particular stimulus in line drawing and photograph see the data file.…”
Section: Resultsmentioning
confidence: 99%
“…It has been showed that there are shorter naming latencies, higher naming accuracy [ 6 , 7 ], and different sources of name disagreement [ 8 ] for photographs than for line drawings. Similarly, in a recent comparison of photographs versus line drawings, Martínez and Matute [ 9 ] showed that children produce better name agreement indices, give fewer incorrect alternative names, and rate as visually more complex the images represented in photographs than in line drawings. Moreover, some researchers have suggested the existence of differences in perceptual processing of photographs versus line drawing, such as, for instance, stronger embodiment representations for photographs of manipulable objects as compared to line drawings [ 10 ].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations